Membangun Kebiasaan Positif: Penerapan 7 Kebiasaan Anak Indonesia Hebat Dalam Dimensi Bermasyarakat Dengan Menerapkan Pembiasaan GEROBAK BAKSO (Gearakan Baik Bakti Sosial) di SDN Pangkah 07 - Maryo Lukito; Hanung Sudibyo; Suriswo Suriswo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to ensure the success of the government's program, the Seven Habits of Great Indonesian Children. On the other hand, character building for students is an important aspect in education. Positive character building is an important foundation for future moral, social, and academic development. Positive habit activities at Elementary School Pangkah 07 were developed through a habit-building program called 'Gerobak Bakso', an abbreviation of Gerakan Baik Bakti Sosial (Good Social Service Movement). The research method used was descriptive qualitative with a case study approach. The research subjects were the principal, teachers, and students in grades I until VI. Data collection techniques included observation, interviews, and documentation of school programs. The results of the study indicate that the implementation of positive habit education at Elementary School Pangkah 07 was carried out in a programmed manner through routine 'Gerobak Bakso' activities.